Hydrodynamic and mass transfer studies of 125 mm centrifugal extractor with 30% TBP/nitric acid system. (November 2015) - Mandal, Kinkar; Kumar, Shekhar; Vijayakumar, V.; Mudali, U. Kamachi; Ravisankar, A.; Natarajan, R.
Abstract: The Indian nuclear power programme was conceived with a three-stage structure in order to utilize the resources optimally with at most importance to fuel reprocessing for closing the fuel cycle. The first stage of Indian nuclear power programme is based on natural uranium fuelled pressurized heavy water reactors to produce the plutonium (Pu) feed for the second stage. The second stage consists of plutonium fuelled fast breeder reactors to produce U-233 from thorium. The third stage envisages development and deployment of U-233 fuelled reactors. In the fuel cycle operations, solvent extraction is a major step for the recovery of uranium and plutonium. Centrifugal extractors plays a vital role in solvent extraction due to their compact size and high throughput. In the present work, the experimental studies for the hydraulic performance were reported for a single stage annular centrifugal contactor of ϕ125 mm rotor for two-phase flow. Maximum throughput with entrainment less than 1% of one phase to the other, of the centrifugal contactor was measured with the A/O ratio 1 to 6 for the three different bottom vane heights of 6, 8 and 10 mm and also for three different annular gaps of 12, 15 and 18 mm. The centrifugal extractor was operated at different speeds ranging from 1200 to 2200 rpm. In addition, mass transfer performance of the same unit was evaluated with 30% TBP/nitric acid biphasic systems. Highlights: A 125 mm dia centrifugal contactor was indigenously designed and developed. Hydraulic performance of this contactor was investigated 30% TBP/nitric acid system. From the results, it was established that the unit had a wide operational window. Mass transfer evaluation resulted in efficiencies of typically 90% and above. It could be used in solvent extraction plants resulting process intensification.